2003
DOI: 10.1177/00207640030493007
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Patients and Patterns of Psychiatric Service Use in Ethnic Minorities

Abstract: Ethnic diversity both in the characteristics of patients and their patterns of psychiatric care should be addressed when planning and developing services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(12 citation statements)
references
References 16 publications
0
11
1
Order By: Relevance
“…Apart from one study conducted in 1963 (Kiev, 1963), all others were conducted between 1998 and 2019. Only five papers focused on the Irish population (Bhui et al., 2008; Breslin & Lewis, 2017; Commander et al., 2003; Cooper et al., 2008; Kerrigan & Green, 2018) and 24 explored the African Caribbean population. Most papers covered other ethnic groups in addition to the African Caribbean or Irish populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from one study conducted in 1963 (Kiev, 1963), all others were conducted between 1998 and 2019. Only five papers focused on the Irish population (Bhui et al., 2008; Breslin & Lewis, 2017; Commander et al., 2003; Cooper et al., 2008; Kerrigan & Green, 2018) and 24 explored the African Caribbean population. Most papers covered other ethnic groups in addition to the African Caribbean or Irish populations.…”
Section: Resultsmentioning
confidence: 99%
“…Two papers grouped the Irish sample with other white minority groups. These studies were retained as they included African and Caribbean samples (Commander et al., 2003; Cooper et al., 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Several factors have been associated with a greater utilisation of mental health services, such as personality factors (Goodwin et al, 2002), sex (Albizu-Garcia et al, 2001;Lindamer et al, 2003), an individuals' recovery style (Tait et al, 2003;Slade et al, 2008), diagnosis (Keown et al, 2005;Mojtabai et al, 2005), socio-economic status (Tansella, 2007) and sociodemographic and clinical characteristics in schizophrenic patients (Carr et al, 2003;Percudani et al, 2003). Furthermore, psychiatric service use by ethnic minorities (Commander et al, 2003) and accessibility and pathways to psychiatric care have also been studied Bhui et al, 2003). An Italian study has confirmed the effects of patients' psychopathology and users' characteristics in the clinicians' dispositional process (Rossi et al, 2006).…”
mentioning
confidence: 99%
“…A further indication that Tudor-Hart's arguments about the inverse care law need to be applied cautiously in relation to mental healthcare is the pattern of MHAC findings on race, age and gender. As we saw earlier from the MHAC report, Black African and Black African-Caribbean patients are over-represented in compulsorily detained parts of the mental healthcare system and we also know that they are under-represented in primary mental healthcare, with its ethos of voluntarism (Nazroo, 2003; Commander et al ., 2003).…”
Section: Controversy About Contemporary Mental Health Workmentioning
confidence: 99%